2024
DOI: 10.2486/indhealth.2022-0174
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting work productivity and activity impairment among chronic obstructive pulmonary disease patients

Abstract: Chronic obstructive lung disease (COPD) can negatively affect patients' employment and work-life activities with a significant indirect economic impact. The current study aimed to measure unemployment, work productivity, activity impairment, and their associated factors among COPD patients. A cross-sectional study was conducted in the Chest outpatient clinic, Mansoura University Hospital, Egypt. COPD patients completed an interviewer-administered questionnaire including sociodemographic, occupational data, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…These findings are consistent with previous research that has shown the impact of employment status on the well-being and functional abilities of individuals with chronic illnesses. For instance, Abdelwahab et al [ 37 ] found that a significant proportion of patients with COPD gave up their jobs due to their condition, highlighting the influence of employment on the lives of individuals with chronic respiratory diseases. Group-based interventions using pulmonary rehabilitation and regular physical activity are needed for unemployed and retired patients with COPD to explore the extent to which reestablishing or maintaining a social connection can improve SCD-related functional limitations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous research that has shown the impact of employment status on the well-being and functional abilities of individuals with chronic illnesses. For instance, Abdelwahab et al [ 37 ] found that a significant proportion of patients with COPD gave up their jobs due to their condition, highlighting the influence of employment on the lives of individuals with chronic respiratory diseases. Group-based interventions using pulmonary rehabilitation and regular physical activity are needed for unemployed and retired patients with COPD to explore the extent to which reestablishing or maintaining a social connection can improve SCD-related functional limitations.…”
Section: Discussionmentioning
confidence: 99%